AGE AND ORIGIN OF FLINT TOOLS OF THE MEZHYRICHCHIA GEOARCHEOLOGICAL MONUMENT (KANIV DNIEPER LOWLAND) - Kovtoniuk, О.; Бортник, С.; Погорільчук, Н.; Ковтонюк, О. (Київський національний університет імені Тараса Шевченка, 2020)
The article clarifies the stratigraphic binding and origin of silicon nodules, which served as the main raw material for the manufacture of tools for mammoth hunters of the Mezhyrich Late Paleolithic site. In archaeological publications, these nodules are often mentioned to be confined to the "Vyrzhikovsky layer" (the Albian layer of the Lower Cretaceous), which was formed under continental conditions and consists of sand-clay (kaolin, in particular) deposits. The analysis of the necessary conditions and possible mechanisms for the formation of silicon nodules indicates the erroneousness of such ideas. Most likely, the source of silicon raw materials was the marine deposits of the Cenomanian (Upper Cretaceous), or, in accordance with the modern stratigraphic division of the Mesozoic-Cenozoic sequence, deposits of the Burim suite (upper Albian – lower Cenomanian). The paleogeographic setting, sedimentological conditions and lithological composition of the "Vyrzhikovsky layer" did not ensure the formation of silicon nodules in it in the form of inclusions. The latter are diagenetic in origin and could only form in the thickness of carbonate rocks, free of clay minerals. The region of Kaniv dislocations was the optimal region from the silicon production point of view, which was determined: firstly, by the tectonic dislocation of the sedimentary sequence, which contributed to the removal of deposits containing silicon nodules in the thickness of younger rocks; secondly,the erosion activity of temporary streams, which brought these deposits to the level of the denudation cut-off. The most convenient place for collecting flints was not the outcrop of bedrock in ravines but the cones of their removal, which overlook the floodplains of the Dnipro and Ros'. The possibility of collecting flint in the immediate vicinity of the Mezhirich site, in the ravines and gullies between the Ros and Rosava rivers, does not find confirmation, since the chalk deposits here lie much lower than the local erosion base and are not exposed by ravines. Therefore, the leading role in the formation of the raw material supply of the Late Paleolithic site of Mezhirich was played by the region adjacent to the Kaniv mountains of the alluvial-proluvial plain.

Присвячено уточненню стратиграфічного положення та походження крем'яних конкрецій, що служили основною сировиною для виготовлення знарядь праці мешканців Межиріцької пізньопалеолітичної стоянки. В археологічних публікаціях зазначається, що ці конкреції приурочені до "шару Виржиківського" (альбський ярус нижньої крейди), який сформувався в континентальних умовах і складений піщано-глинистими (зокрема каоліновими) відкладами. Проведений аналіз необхідних умов і можливих механізмів формування крем'яних конкрецій свідчить про помилковість таких уявлень. Імовірніше, джерелом крем'яної сировини були морські відклади сеноману (верхня крейда) або, за сучасним стратиграфічним поділом мезозой-кайнозойської товщі, відклади бурімської світи (верхній альб – нижній сеноман). Палеогеографічна обстановка, седиментаційні умови та літологічний склад "шару Виржиківського" не могли забезпечити формування в ньому включень крем'яних конкрецій. Останні є діагенетичними за походженням і могли утворитися тільки в карбонатних породах, що не містять глинистих мінералів. Район Канівських дислокацій був оптимальним регіоном щодо добування кременю. Цьому сприяли: 1) тектонічна дислокованість осадової товщі, яка вивела кременевмісні шари в товщу молодших покривних відкладів; 2) ерозійна діяльність тимчасових водотоків, яка сприяла виходу цих шарів на денну поверхню. Але найзручніше мисливцям на мамонтів було збирати кремені не у відслоненнях корінних порід, а в пухких пролювіальних відкладах конусів виносу ярів, які виходили на заплави Дніпра та Росі. Можливість видобування крем'яної сировини безпосередньо поблизу Межиріцької стоянки, в ярах і балках межиріччя Росі та Росави, де в геологічному розрізі присутні крейдові відклади, видається сумнівною, адже вони залягають тут нижче рівня місцевого базису ерозії й не відслонюються в ярах. Тому у формуванні сировинної забезпеченості пізьопалеолітичної стоянки Межиріч провідну роль відіграв саме район прилеглої до Канівських гір алювіально-пролювіальної рівнини.
ПРО ВІК І ПОХОДЖЕННЯ КРЕМ'ЯНОЇ СИРОВИНИ ІНВЕНТАРЮ ГЕОАРХЕОЛОГІЧНОЇ ПАМ'ЯТКИ МЕЖИРІЧ (КАНІВСЬКЕ ПРИДНІПРОВ'Я)
Keywords: геоархеологія; Межиріч; крем'яні конкреції; шар Виржиківського; geoarchaeology; Mezhirich; silica nodules; Virzhikovsky layer